2014
DOI: 10.2340/00015555-1647
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Botulinum Toxin Dose with Neurophysiological Parameters of Efficacy and Safety in the Glabellar Muscles: A Double-blind, Placebo-controlled, Randomized Study

Abstract: Despite the extensive use of botulinum toxin type A (BoNT-A) in treatments for glabellar frown lines, the dose-response effect in the glabellar muscles remains unknown. The aim of this randomized, double-blind, placebo-controlled prospective study was to characterize the neurophysiological parameters that correlate with the effect of BoNT-A in the glabellar muscles and its diffusion to surrounding ocular muscles. Sixteen healthy women were recruited and randomized to 3 different dose-groups of onabotulinumtoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The CMAP amplitude has previously been reported to be an appropriate neurophysiological parameter for evaluation of the dose–response effect of botulinum toxin injections in the facial muscles of the glabellar area. 11 In our study, CMAP results also demonstrate that the twofold injection volume of 0.1 mL of abobotulinumtoxinA is noninferior to the 0.05 mL labeled injection volume in delivering the 10 sU fixed dose.…”
Section: Discussionsupporting
confidence: 68%
“…The CMAP amplitude has previously been reported to be an appropriate neurophysiological parameter for evaluation of the dose–response effect of botulinum toxin injections in the facial muscles of the glabellar area. 11 In our study, CMAP results also demonstrate that the twofold injection volume of 0.1 mL of abobotulinumtoxinA is noninferior to the 0.05 mL labeled injection volume in delivering the 10 sU fixed dose.…”
Section: Discussionsupporting
confidence: 68%
“…It is well known that the local effect of BoNT/A intramuscular injection either clinically (muscle paralysis) or through single-fiber electromyography (SFEMG) demonstrates very high jitter and impulse blocking [11][12][13][14]. The BoNT/A injection also may spread nearby, causing weakness, as seen in cervical dystonia (dysphagia) and in blepharospasm and hemifacial spasm (eyelid drop), that usually takes a few days to clear up [15]. Another defined point is the adjacent, and distant BoNT/A effect detected only through SFEMG with high jitter without or with sparse impulse blocking [11,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The first study found that reduction of the CMAP amplitude measured over the corrugator supercilii correlates well with intramuscular dose of onabotulinumtoxin A (Vistabel ® ) in the same muscle [ 50 ]. Further, electromyography (EMG) measurements revealed the onset of muscle paralysis after two weeks and effects (denervation) lasting as long as 24 weeks after injection in individuals receiving a high dose of onabotulinumtoxin [ 50 ]. Importantly, this study supports a novel neurophysiological strategy for effect evaluation of BoNT in glabellar muscles, since both CMAP and EMG parameters correlated with BoNT dose.…”
Section: Neurophysiological Measures Of Bont Effect In Facial Muscmentioning
confidence: 99%
“…Following injections of the glabellar muscles for the indication glabellar lines, limited diffusion is known to occur to the surrounding extraocular muscle orbicularis oculi. This diffusion can be detected as slightly disturbed neuromuscular transmission (jitter) with single-fibre electromyography [ 50 ]. Diffusion has also been reported to contralateral facial muscles following unilateral BoNT application [ 74 ].…”
Section: Considerations To “Split Face” Design: Spread Of Bont In mentioning
confidence: 99%